SUSTAINABILITY OF THE FINANCIAL SYSTEM WITHOUT INTEREST RATES - Paunović, Miloš (Economic Outlook, 2022)
The emergence of periodic economic and financial crises requires taking concrete economic policy measures to overcome the crisis and repair its consequences. Whether these measures are adequate or only over time lead to the emergence of a new crisis, or whether the crisis is coded in the economic system, this paper analyzes from the angle of interest rates. As interest rates condition the exponential growth of indebtedness, and therefore the world economy is increasingly burdened with interest allocations, this implies the conclusion that the crisis is systemic and will take on increasing proportions over time. According to this assumption, the sustainability of the financial system based on interest rates is questionable and therefore the possibility of applying and sustainability of the financial system without interest rates should be considered.
Keywords: money, debt, interest, money without interest, free money